Trends and Financial Variations in Executive Confidence: A Decade-Long Analysis - Diksha SAINI; Balwinder SINGH (Eurasian Journal of Business and Economics)
The present research is an endeavour to measure the extent of overconfidence bias among Chief Executive Officers (CEOs) in India. Additionally, this investigation seeks to examine the financial disparities among firms led by CEOs exhibiting different levels of overconfidence. This study is based on a sample of 500 large Indian companies listed on the Bombay Stock Exchange over a period of twelve years starting from 2009-2010 to 2020-2021. The findings reveal a downward trend in the overconfident behaviour of CEOs over the specified period, with notable exceptions during key corporate events like the introduction of the Companies Act in 2014 and the COVID-19 pandemic. Moreover, the t-test and ANOVA estimation results unveil that firms led by CEOs with different overconfidence levels have significant variations in their returns, size, age, liquidity, and growth. The study offers valuable insights into behavioural finance literature and serves board members, investors, and policymakers by expanding the understanding of executive psychology within the Indian context. Additionally, to the best of the authors’ knowledge, this present study is the first to analyse the decade-long trends and financial implications of cognitive attributes of top executives in the Indian corporate sector.